Zwitterionic structures: from physicochemical properties toward computer-aided drug designs. (December 2016) - Yang, Zhiwei; Li, Qinyi; Yang, Gang
Zwitterions, used widely in chemical, biological and medicinal fields, show distinct physicochemical properties relative to ordinary ampholytes, which largely decide their bioavailability and biological activities. In the present manuscript, these properties are discussed in order to facilitate our understanding of zwitterionic structures, followed by various examples of zwitterionic drugs and the critical role these properties play. We specifically focus our discussions on neuraminidase inhibitors (NAIs), which are used in the treatment and prevention of influenza, covering their computer-assisted design, transformation to zwitterionic isomers and interaction mechanisms of NAIs with proteins. The discovery and development of NAIs provide useful insights that may assist in the exploration of new zwitterionic drugs. Graphical abstract: